Tribute – Brian Gannon 1939 - 2017 - Merle Allsopp (Scottish Journal of Residential Child Care)
As we trace the threads of all of our different relationships with Brian today, we all know and celebrate different facets of this most talented man…Brian the musician, Brian the artist, Brian the writer, the editor, the publisher, Brian the mentor and Brian the friend.